363. Acute Kidney Injury and Renal Replacement Therapy in Hospitalized COVID-19 Patients in the United States and Other Geographic Regions. (31st December 2020) - Gilbert, Shannon NovosadShannon NovosadLeah; Apata, Ibironke W; Overton, Rahsaan; Garg, Shikha; Kim, Lindsey; Jackson, Brendan R; Patel, Priti
Abstract: Background: Acute kidney injury (AKI) is a complication that has been described among severely ill patients with COVID-19 and may be more common in those with underlying chronic kidney disease (CKD). Some patients with AKI require renal replacement therapy (RRT), including continuous RRT (CRRT). During the COVID-19 pandemic, some US areas experienced CRRT supply shortages. We sought to describe the percent of hospitalized COVID-19 patients who developed AKI or needed RRT to inform patient care and resource planning. Methods: We searched for studies in the literature and public health investigations that described CKD, AKI, and/or RRT in COVID-19 patients from January 2020 onward. Studies were excluded if no CKD, AKI, or RRT information was provided. We abstracted counts of hospitalized COVID-19 patients, including those admitted to intensive care units (ICU) who developed AKI, underwent RRT, and/or had CKD. Data were pooled across cohorts by geographic region with available data (US, China, or United Kingdom [UK]). We compared proportions using Chi-square tests. Results: A total of 311 studies were identified; 23 studies (US n=11; China n=11; UK n=1) that described kidney disease and/or kidney-related outcomes in hospitalized COVID-19 patients were included. Underlying CKD prevalence was higher in US cohorts (10.3%) compared with China (2.5%) or UK (1.5%) (p< 0.0001). AKI was markedly higher among hospitalized (31.3% vs. 6.4%; p < 0 .001) and ICU patients (55.4% vs. 18.2%; p< 0.0001) in the US compared to China. The percent of ICU patients requiring RRT in the US (16.8%) was significantly different from that reported in China (12.5%) and the UK (23.9%) (p< 0.0001). Limitations include differences in CKD and RRT definitions across studies. Conclusion: AKI is a frequent outcome among US COVID-19 patients, affecting almost one third of hospitalized and more than half of ICU patients. AKI was reported more frequently in the US than China. The percent of ICU patients who received RRT was higher in the US and UK than in China. Understanding the occurrence of kidney-related outcomes among patients with COVID-19 including the impact of underlying CKD and regional practice variations is essential for healthcare systems to successfully plan for RRT needs during the pandemic. Disclosures: All Authors : No reported disclosures